Digitalization of the Legal System: Opportunities and Challenges for Indonesia: Digitalisasi pada Sistem Hukum: Peluang dan Tantangan bagi Indonesia - Multazam, Mochammad Tanzil; Widiarto, Aan Eko (Universitas Muhammadiyah Sidoarjo, 2023)
This study aims to analyze the impact and challenges of digitalization in the Indonesian legal system, focusing on its implications for legal education, data security, and professional readiness. Adopting a qualitative approach, the research synthesizes discussions on the evolution of legal processes in response to technological advancements. Findings highlight that digitalization offers efficiencies and transparency yet poses significant cybersecurity risks. The study underscores the urgent need for enhanced digital literacy and legal education reform, emphasizing skills in AI and blockchain technology. The implications of this study are pivotal for policymakers and educators as they navigate the balance between embracing digital innovation and addressing the associated risks in the legal domain. Highlights: Digital Technologies' Impact: Digitalization, especially through the E-Court program, significantly enhances the efficiency and transparency of legal processes in Indonesia. Challenges in Implementation: Key obstacles include the digital divide between urban and rural areas, slow adaptation of legal frameworks, and concerns over data privacy and cybersecurity. Need for Strategic Governance: Effective digital transformation in the legal system requires comprehensive strategies, improved cybersecurity, and the adaptation of legal professionals to technological advancements. Keywords: Digitalization, Indonesian Legal System, Big Data, Blockchain, Artificial Intelligence